The substitution of glycine 661 by arginine in type III collagen produces mutant molecules with different thermal stabilities and causes Ehlers-Danlos syndrome type IV. Issue 8 (August 1993) - Richards, A; Narcisi, P; Lloyd, J; Ferguson, C; Pope, F M
Abstract : Previous studies have shown that Ehlers-Danlos syndrome type IV (EDS IV) is caused by mutations of type III collagen (COL3A1). Here we have characterised the most amino-terminal glycine substitution so far described in a patient with EDS IV. A combination of peptide mapping and chemical cleavage analysis of cDNA localised the mutation in cyanogen bromide peptide CB5. Sequence analysis showed a G to A mutation, converting glycine 661 to arginine, which was a new dominant mutation. Analysis of type III collagen secreted by cultured fibroblasts showed an overmodified mutant protein with normal thermal stability. However, the intracellularly retained form melted 2 degrees C lower than normal. This indicated that molecules resulting from the same mutation can differ in their thermal stabilities.